Trimodality Therapy in the Treatment of Stage III N2‐Positive Non‐Small Cell Lung Cancer: A National Cancer Database Analysis. (14th January 2020) - Behera, Madhusmita; Steuer, Conor E.; Liu, Yuan; Fernandez, Felix; Fu, Chao; Higgins, Kristin A.; Gillespie, Theresa W.; Pakkala, Suchita; Pillai, Rathi N.; Force, Seth; Belani, Chandra P.; Khuri, Fadlo R.; et al.
Abstract: Background: Significant controversy remains regarding the care of patients with clinical stage III (N2‐positive) NSCLC. Although multimodality therapy is effective, the roles of surgery, chemotherapy, and radiotherapy are not fully defined and the optimal treatment approach is not firmly established. We analyzed outcomes and predictors associated with trimodality therapy (TT) in the National Cancer Database. Materials and Methods: The NCDB was queried from 2004 to 2014 for patients with NSCLC diagnosed with stage III (N2) disease and treated with chemotherapy and radiation (CRT). Three cohorts of patients were studied: CRT only/no surgery (NS), CRT plus lobectomy (LT), and CRT plus pneumonectomy (PT). The univariate and multivariable analyses (MVA) were conducted using Cox proportional hazards model and log‐rank tests. Results: A total of 29, 754 patients were included in this analysis: NS 90.1%, LT 8.4%, and PT 1.5%. Patient characteristics: median age 66 years; male 56% and white 85%. Patients treated at academic centers were more likely to receive TT compared with those treated at community centers (odds ratio: 1.85 [1.53–2.23]; p < .001). On MVA, patients that received TT were associated with better survival than those that received only CRT (hazard ratio: 0.59 [0.55–0.62]; p < .001). The LT group was associated with significantly better survival than the PT and NS groups (median survival: 62.8 months vs. 51.8 months vs. 34.2 months, respectively). In patients with more than two nodes involved, PT was associated with worse survival than LT and NS (median survival: 51.4 months in LT and 39 months in NS vs. 37 months in PT). The 30‐day and 90‐day mortality rates were found to be significantly higher in PT patients than in LT. Conclusion: TT was used in less than 10% of patients with stage III N2 disease, suggesting high degree of patient selection. In this selected group, TT was associated with favorable outcomes relative to CRT alone. Implications for Practice: This analysis demonstrates that trimodality therapy could benefit a selected subset of patients with stage III (N2) disease. This plan should be considered as a treatment option following patient evaluation in a multidisciplinary setting in experienced medical centers with the needed expertise. Abstract : This study researched new diagnoses of non‐small cell lung cancer in the U.S. to evaluate outcomes and predictors associated with trimodalilty therapy‐surgery, radiotherapy, and chemotherapy.